2022
DOI: 10.1186/s12877-022-03062-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and associated factors of older persons in sub-Saharan Africa: a scoping review

Abstract: Background The older person population is rapidly increasing globally, including sub-Saharan Africa (SSA). Concurrently, malnutrition is also increasing among older persons in SSA, with a dearth of empirical evidence on nutritional status and associated factors among the older persons in the region to inform effective interventions to promote healthy ageing. Aim/Objective This review assessed the nutritional status and associated factors among olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
3
20
1
Order By: Relevance
“…However this high prevalence of under nutrition calls for closer attention to the nutrition of elderly people. The results for this study however falls within the range for underweight prevalence among elderly people as found in a review of studies in Africa [9]. It is also less than the values gotten from a study from a national survey in Bangladesh.…”
Section: Discussioncontrasting
confidence: 82%
“…However this high prevalence of under nutrition calls for closer attention to the nutrition of elderly people. The results for this study however falls within the range for underweight prevalence among elderly people as found in a review of studies in Africa [9]. It is also less than the values gotten from a study from a national survey in Bangladesh.…”
Section: Discussioncontrasting
confidence: 82%
“…The factors considered were taken from a review that assessed the nutritional status and associated factors among older individuals in sub-Saharan Africa and a study conducted to assess dietary diversity among older adults in Zambia. 15 Accordingly, from the prevalence (645) and factors’ (128) sample sizes, the largest sample size (645) was considered for the final. The study area was stratified into urban and semiurban areas.…”
Section: Methodsmentioning
confidence: 99%
“…The MNA Short Form or the full-length screening tool (18 items)15–17 should be employed, as both have been validated for use in malnutrition screening among the elderly population. The MNA aids in the early detection of malnutrition before it progresses to severe malnutrition with protein depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people are at nutritional risk not only because of physiological changes but also because of inadequate food intake, which can result in macro-and micronutrient deficiencies. 11 Poor quality of diets is the leading cause of macro-and micronutrient deficiencies in sub-Saharan Africa. 12 In African countries, several studies reported limited research on the health and well-being of the elderly, and interventional strategies to address the needs of this group are poorly articulated.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people are at nutritional risk not only because of physiological changes but also because of inadequate food intake, which can result in macro- and micronutrient deficiencies. 11 Poor quality of diets is the leading cause of macro- and micronutrient deficiencies in sub-Saharan Africa. 12 …”
Section: Introductionmentioning
confidence: 99%